PELATIHAN INTEGRASI TARUNA WREDA NUSANTARA DALAM PENGEMBANGAN KEMAMPUAN KEPEMIMPINAN DAN PENDIDIKAN DI KABUPATEN LOMBOK - Sigit Saksono; Aris Basuki (PPM Sdirjianbang Akademi Militer, 2022)
The Integration Training of Taruna Wreda Nusantara is a form of Community Service (PkM) as an implementation of the Tri Dharma of Higher Education which is an academic activity that must be carried out by all universities including the Military Academy in accordance with the National Higher Education Standards. The purpose of the Taruna Wreda Nusantara Integration Exercise is to utilize science and technology to improve people's welfare and educate the nation's life and increase the nation's competitiveness. Thus the implementation of the Taruna Wreda Nusantara Integration Exercise is expected to be carried out continuously. This service uses a community social activity approach by building public facilities, providing socialization of national insight for the community where the service is held and counseling on the cultivation of the value of struggle. The method used is Karya bhakti and socialization to the community around Lombok, NTB for 35 days. With this service activity, community difficulties can be overcome and the economy can increase